Integrating Ribosomal Promoter Vectors that Offer a Choice of Constitutive Expression Profiles in Leishmania donovani - Soysa, Radika (Mol Biochem Parasitol, 2016)
We have designed a novel series of integrating ribosomal RNA promoter vectors with five incrementally different constitutive expression profiles, covering a 250-fold range. Differential expression was achieved by placing different combinations of synthetic or leishmanial DNA sequences upstream and downstream of the transgene coding sequence in order to modulate pre-mRNA processing efficiency and mRNA stability, respectively. All of the vectors have extensive multiple cloning sites, and versions are available for producing N- or C- terminal GFP fusions at each of the possible relative expression levels. In addition, the modular configuration of the vectors allows drug resistance cassettes and other components to be readily exchanged. In toto, these vectors should be useful additions to the toolkit available for molecular and genetic studies of Leishmania donovani.